Reforestation of Lebanon cedar (Cedrus libani A. Rich.) in bare karstic lands by broadcast seeding in Turkey - Boydak M. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
The objective of this article is to explain the application of broadcast seeding method with Lebanon cedar in bare karstic lands with shallow or medium soil depth and with bedrock creaks, which resulted from the destruction of Lebanon cedar since 5000 years in the Taurus Mountain range, Turkey. The idea of planting by broadcast seeding was first recommended by Boydak, in 1983 in Armutkýrý, Anamur, Turkey. Based on his report, Turkish Forest Service prepared a reforestation project and broadcast seeding of Lebanon cedar was applied in 300 ha, in the fall of 1984, for the first time. The result was very successful and at the end of fifth growing season an average of one seedling per sqm (9000 seedlings per ha) was obtained. This application was considered a breakthrough and between 1984-2005, Turkish Forest Service has planted 40.457 ha Lebanon cedar by broadcast seeding in bare karstic lands in Taurus Mountains. Research results reveal that the amount of seeds with cone scales to be dispersed varied between 200 kg/ha and 600 kg/ha, depending on ecological sites, exposures and surface soil tillage (between 10-20 cm; at compact soils). Considering research and application results, recommendations were made for broadcast seeding application of Lebanon cedar in bare karstic lands.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)